2002
DOI: 10.2134/agronj2002.1257
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Effects on Herbage Mass and Composition in Grass–Birdsfoot Trefoil Mixtures

Abstract: Grass–legume mixtures have the ability to supply more consistent forage yields across a wide range of environments throughout the grazing season than do grass monocultures. The suitability of diverse grass species in binary mixtures with birdsfoot trefoil (Lotus corniculatus L.) in rotational stocking systems has not been extensively studied. The objective of this study was to evaluate binary mixtures of five cool‐season grasses with the birdsfoot trefoil cultivar Norcen for herbage mass, botanical composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…For northern areas of Europe, in addition to an extended role for red clover under grazing, recent experience with birdsfoot trefoil ( Lotus corniculatus) suggests there is considerable potential for this species particularly in low‐input systems and to take advantage of its nutritional properties associated with condensed tannins (Alison and Hoveland, 1989; Douglas et al. , 1995; Leep et al. , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For northern areas of Europe, in addition to an extended role for red clover under grazing, recent experience with birdsfoot trefoil ( Lotus corniculatus) suggests there is considerable potential for this species particularly in low‐input systems and to take advantage of its nutritional properties associated with condensed tannins (Alison and Hoveland, 1989; Douglas et al. , 1995; Leep et al. , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the production benefits of forage legumes, their forage nutritive value is important. This potential for yield compensation by legumes can be instrumental in improving the seasonal distribution of forage and increasing the capacity of a pasture to support livestock grazing throughout the summer (Leep et al, 2002;Lauriault et al, 2006). Multiple studies have shown that grass-legume mixtures improve crude protein (CP) and neutral detergent fiber (NDF) content in forage compared with the grass monocultures (Malhi et al, 2002;Zemenchik et al, 2002;Kopp et al, 2003;Deak et al, 2007;Kleen et al, 2011) Forage legumes commonly used in grass-legume mixtures, such as alfalfa (Medicago sativa L.) (ALF) and birdsfoot trefoil (Lotus corniculatus L.) (BFTF), are productive during summer months when cool-season grass production is low.…”
mentioning
confidence: 99%
“…Hay management differs from grazing in selectivity (Edwards et al, 1996) and is typically less frequent in defoliation (Beuselinck et al, 1994). Animal selectivity of regrowth can lead to overgrazing of some species or areas, permitting invasion by non‐planted species, while other areas or species are underutilized (Barker et al, 2002; Beuselinck et al, 1994). Additionally, grazing animals can leave shorter stubble if forced to maximize forage utilization (Beuselinck et al, 1994), exposing susceptible plant parts to excessive heat or light (Harris et al, 1999).…”
mentioning
confidence: 99%